One‐year bleaching efficacy using two HP products with different pH: A double‐blind randomized clinical trial. Issue 5 (13th June 2019) - Bersezio, Cristian; Martín, Javier; Prieto, María V.; Meneses, Pablo; Angel, Pablo; Eduardo Fernández, G.; Loguercio, Alessandro
Abstract: Objectives: This split‐mouth, double‐blind, randomized clinical trial evaluated the 1‐year bleaching efficacy produced by two hydrogen peroxide gels with different pHs. Materials and Methods: Twenty‐eight patients were divided into two groups corresponding to two different products: Pola Office (pH = 2.0/SDI) and Pola Office Plus (pH = 7.0/SDI). The treatment was assessed during and after the bleaching procedure up to 12 months post‐treatment. The assessment consisted of two bleaching scales shade guide units (ΔSGU) and spectrophotometric device (Δ E, ΔE00, and Whiteness Index) of both maxillary quadrants. Results for ΔSGUs in both scales and ΔE00 and Whiteness Index were compared using Mann Whitney test and Δ E measurements through the t ‐Student test for paired samples in each evaluation time. The color rebound (1‐ vs 12‐month postbleaching data) was evaluated with Wilcoxon test (alpha = .05). Results: During the different times of evaluation, the color variation was similar for both products ( P > .05), both for subjective (ΔSGUs) and objective assessments (Δ E, ΔE00, and Whiteness Index). Also, both products showed a slight rebound after 12‐month postbleaching ( P > .05). Conclusions: Concerning the stability of color, in‐office dental whitening with two hydrogen peroxide gels of different pHs produced similar results, with no significant of regression, for 12 months postwhitening. Clinical Significance: Bleaching using a neutral (pH = 7.0) in‐office gel demonstrated similar stability and rebound effect than an acidic one (pH = 2.0).